Empresas transnacionais brasileiras de origem familiar: a governança corporativa como mecanismo de controle de gestão - Silva, Alessandra Mendes da (2010)
The aim of this study was to analyze the problematical situation of Brazilian family owned companies; they are used to running their business in a centralized manner (Family Control System) with the phenomenon of internationalizing their operations they had to change the way of managing their business and adopting the decentralized system so that they can participate in the competitive international market. With internationalization these companies face challenges to adapt to the different cultural, political and socio-economical environment of the countries they want to operate in, making it difficult to maintain the way their family conglomerate managed the business up till now.However, changing the system of management control for these Brazilian companies because of their family story and or origin impacts in the institutional culture of these companies, as well as to bring insecurity to the controlling family that has always been used to centralizing the management of their business. As a mechanism to solve this problem, there has been the rise of the best practices of corporative administration in these companies as a management instrument for these controlling families to run their operations overseas